2014
DOI: 10.3892/ol.2014.1807
|View full text |Cite
|
Sign up to set email alerts
|

miR-203 inhibits tumor cell migration and invasion via caveolin-1 in pancreatic cancer cells

Abstract: Pancreatic cancer is one of the most lethal malignant diseases with the poorest prognosis and is the fourth leading cause of tumor-associated mortality in the industrialized world. microRNAs (miRNAs or miRs) are small noncoding RNAs of approximately 22 nucleotides long that are able to function as oncogenes or tumor suppressors in human cancer. In our study, overexpression of miR-203 in Panc-1 cells is sufficient to reduce migratory ability and invasiveness, and to induce upregulation of epithelial markers (Sn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 18 publications
3
39
0
Order By: Relevance
“…Whether miRNAs act as oncogenes or tumor suppressor genes depends on the context. For example, miR-203 behaves as a tumor suppressor and is downregulated in pancreatic, glioma and esophageal cancer, while it is upregulated in epithelial ovarian cancer and acts as an oncogene (9,(20)(21)(22). The present study demonstrated that miR-203 was downregulated in NSCLC specimens, which is in agreement with a …”
Section: Discussionsupporting
confidence: 81%
“…Whether miRNAs act as oncogenes or tumor suppressor genes depends on the context. For example, miR-203 behaves as a tumor suppressor and is downregulated in pancreatic, glioma and esophageal cancer, while it is upregulated in epithelial ovarian cancer and acts as an oncogene (9,(20)(21)(22). The present study demonstrated that miR-203 was downregulated in NSCLC specimens, which is in agreement with a …”
Section: Discussionsupporting
confidence: 81%
“…In addition, we demonstrated that overexpressed miR-203 improved gemcitabine sensitivity; a finding consistent with other data which showed that miR-203 inhibits cell proliferation and invasiveness in prostate carcinoma, and induces apoptosis in transitional cell carcinom (38). Moreover, Feber et al revealed that miR-203 suppresses cell proliferation in esophageal carcinoma (22), while Miao et al showed that miR-203 inhibits cell migration, invasion, and the epithelial-mesenchymal transition (EMT) via caveolin-1 in pancreatic carcinoma (39). Considering these data, our results support the hypothesis that miR-203 acts as a tumor suppressor gene by regulating Puma expression in both colon and lung cancer cells.…”
Section: Overexpressed Mir-203 Induces Apoptosis and Decreases Cell Isupporting
confidence: 78%
“…These data suggest that oridonin preferentially be an anti-OvCa reagent. Further, we examine whether oridonin affected cell cycle progression and apoptosis and our results revealed that it induced a Oridonin inhibits migration, invasion of SKOV3 cells Tumor migration and invasion are the essential steps in tumorigenesis (Miao et al, 2014). We determined the effects of oridonin on the chemotactic motility of SKOV3 cells using wound-healing migration and transwell cell invasion assays.…”
Section: Inhibition Of Ovarian Cancer Cell Lines Proliferation By Orimentioning
confidence: 99%